Increased Neurofilament Light Chain and YKL-40 CSF Levels in One Japanese IBMPFD Patient With VCP R155C Mutation: A Clinical Case Report With CSF Biomarker Analyses - Ikeda, Masaki; Kuwabara, Takeo; Takai, Eriko; Kasahara, Hiroo; Furuta, Minori; Sekine, Akiko; Makioka, Kouki; Yamazaki, Tsuneo; Fujita, Yukio; Nagashima, Kazuaki; Higuchi, Tetsuya; Tsushima, Yoshito; et al. (Frontiers in Neurology, 2020)
Inclusion body myopathy (IBM) with Paget's disease of bone (PDB) and frontotemporal dementia (IBMPFD) presents with multiple symptoms and an unknown etiology. Valosin-containing protein (VCP) has been identified as the main causative gene of IBMPFD. However, no studies on neurofilament light chain (NFL) as a cerebrospinal fluid (CSF) marker of axonal neurodegeneration or on YKL-40 as a CSF marker of glial neuroinflammation have been conducted in IBMPFD patients with VCP mutations. A 65-year-old man presented with progressive muscle atrophy and weakness of all limbs, non-fluent aphasia, and changes in personality and behavior. Cerebral MRI revealed bilateral frontal and temporal atrophy. 99mTc-HMDP bone scintigraphy and pelvic CT revealed remodeling changes and active osteoblastic accumulations in the right medial iliac bone. Muscle biopsy demonstrated multiple rimmed vacuoles in muscle cells with myogenic and neurogenic pathological alterations. After the patient was clinically diagnosed with IBMPFD, DNA analysis of the VCP gene revealed a cytosine (C) to thymine (T) (C→ T) mutation, resulting in an amino acid exchange of arginine to cysteine (p.R155C mutation). The CSF levels of NFL at two time points (12 years apart) were higher than those in non-dementia controls (CTR) and Alzheimer's disease (AD); lower than those in frontotemporal dementia with motor neuron disease (FTD-MND); and comparable to those in patients with behavioral variant frontotemporal dementia (bvFTD), progressive supranuclear palsy (PSP), and corticobasal syndrome (CBS). The CSF levels of YKL-40 were comparable at both time points and higher than those in CTR; lower than those in FTD-MND; and comparable to those in bvFTD, PSP, CBS, and AD. The CSF levels of phosphorylated tau 181 (P-Tau) and total tau (T-Tau) were not significantly different from those in CTR and other neurodegenerative diseases, except those in AD, which were significantly elevated. This is the first report that demonstrates increased NFL and YKL-40 CSF levels in an IBMPFD patient with a VCP mutation (p.R155C); NFL and YKL-40 levels were comparable to those in bvFTD, PSP, CBS, and AD and higher than those in CTR. Our results suggest that IBMPFD neuropathology may involve both axonal neurodegeneration and glial neuroinflammation.